PERCEIVED EFFECT OF CLIMATE CHANGE ON PRODUCTIVE AND REPRODUCTIVE PERFORMANCE OF DAIRY ANIMALS IN CHATTISGARH (Indian Journal of Animal Production and Management, 2014)
Livestock in India is an integral component for the livelihood resource of poor farmers. Majority of the milk production in India is contributed by the small and marginal farmers who are very prone to face brunt of undesirable’s effects of climate change. Change in climate affects the livestock in many ways such as retardation of animal growth, low quality animal products including hides and skins and increase in livestock diseases. Livestock productivity has been severely affected by vector-borne livestock diseases such as trypanosomiasis, theileriasis, and R.V. fever etc also known as climate sensitive diseases6. Reproductive performance of animals is highly affected by climate variability. Long duration of summer causes heat stress in animal, effect the ova formation in animal and causes sterility. High variations in environment temperatures may compromise reproductive efficiency of farm animals in both sexes and hence negatively affect reproductive performance of livestock. Data were collected personally through interview schedule from 120 tribal respondents of 6 villages of Bodla block of Kabirdham district of Chhattisgarh state. The study revealed that more than 50 per cent respondents perceived reduction in milk yield as well as its persistency due to change in climate attributes. Majority of respondents perceived decrease in length and intensity of estrous period, increase in number of services per conception, age of first calving interval, service period, anestrous and repeat breeding.
Keywords: Reproductive and Productive Performance; Climate change; Dairy animals